Constructing the cascade of HIV care: methods for measurement. Issue 1 (January 2016) - Haber, Noah; Pillay, Deenan; Porter, Kholoud; Bärnighausen, Till
Abstract : Purpose of review: Although the concept of the HIV treatment cascade has reached nearly ubiquitous acceptance in international HIV policy and research, methods for estimating it vary drastically. These variations become increasingly important as the focus of the HIV response shifts from emergency response to long-term outcomes and financial and organizational sustainability. We review the history of the cascade and the current literature and develop the first comprehensive typology of cascade scope and methods. Recent findings: We define the cascade scope in terms of both breadth (range from first to final event) and depth (given breadth, number of cascade stages that analyzed). We distinguish cascade measurement according to four dimensions: denominator–denominator linkage (data used for cascade construction are linked at the individual level across stages); denominator–numerator linkage (data are linked at the individual level within each stage); single vs. multiple populations from which data sources are drawn; and longitudinal vs. cross-sectional design. Summary: Everything else equal, we would prefer broader and deeper cascades, denominator–denominator linkage, denominator–numerator linkage, single population, and longitudinal data over their respective alternatives. Increased investments in population-based cohorts and data linkage are required to complement clinical cohorts for 'broad' longitudinal cascade analyses.